Effects of a structured educational program on nursing students' level of knowledge and awareness toward child neglect and abuse: A quasi-experimental evaluation - Öztürk, Ayfer; Öztürk, Ayfer (Wiley, 2024)
Background: Nurses have a key role in the recognition, reporting, and channelization of child abuse and neglect. Nurses should have sufficient knowledge about the presentation of child abuse and neglect. They also need to understand their role in reporting any instance where they detect cases of abuse and neglect. Purpose: The aim of this study is to determine the effect of a structured Child Neglect and Abuse Educational Program (CNaA-EP) on the level of knowledge and awareness of nursing students about child neglect and abuse. Methods: This study conducted with nursing students used a pretest-post-test quasi-experimental design. The third-year nursing students were divided into two groups: experimental (n = 25) and control groups (n = 30). The intervention group received CNaA-EP. In both groups, pretests were performed using the Child Abuse and Neglect Awareness Scale, and Child Abuse and Neglect Knowledge Test The posttest was conducted 1 week after the 14-week CNaA-EP course was completed. Numbers, percentages, chi-square test, t-test, Kolmogorov-Smirnov test, Fisher's exact test were conducted using SPSS 22.00 software. Results: The education group's scores of child abuse/neglect awareness (t = -2.768 p < 0.05) and child abuse/neglect knowledge (t = -12.416 p < 0.01) were significantly higher than those of the control group. After the education program, a significant difference was found between the education and control groups on the core measures. Conclusion: A child neglect and abuse education program was an effective method of educating nursing students on knowledge and awareness of child abuse and neglect. For this reason, education programs should be planned and implemented to increase awareness about abuse and neglect problems that threaten children's health and development.
Keywords: Awareness; Child Abuse; Child Neglect; Education; Gender; Nursing Student